TRADE DEPENDENCE AND FOOD SECURITY: A COMPARATIVE ANALYSIS OF THE WHEAT SECTOR IN EUROPE - Grujić Vučkovski, Biljana; Grubor, Aleksandar; Ćurčić, Nikola V. (Economics of Agriculture, 2025)
This study explores regional disparities in three key indicators of agri-food security related to wheat across Europe: the Import Dependency Ratio (IDR), the Self Sufficiency Ratio (SSR), and wheat consumption per capita (Cpc). The analysis was conducted at two levels: (1) Europe as a whole, based on a sample of 10 annual observations, and (2) 35 individual European countries, comprising a panel of 350 observations for the period 2014–2023. To compute the aforementioned indicators, the study draws on four primary variables related to wheat: production (tonnes), import volume (tonnes), export volume (tonnes), and population size (in thousands). Descriptive statistical methods were first applied, including the coefficient of variation (Cv) following logarithmic transformation, Pearson correlation coefficients, scatter plots and heatmap. The main objective of this research is to examine the interrelationships between wheat security indicators and key demographic and economic factors across Europe.